Changes in Victorian entrepreneurship in England and Wales 1851-1911: Methodology and business population estimates. Issue 7 (28th September 2022) - Bennett, Robert J.; Smith, Harry; Montebruno, Piero; van Lieshout, Carry
Abstract: The full population of England and Wales employers and own-account business proprietors is estimated using population censuses 1851–1911. The main contribution of the article is a method of mixed single imputation to overcome the challenge of non-responses to the census 1851–1881. This method is compared with alternatives. Downloads of all data allow replication. The method is used to track trends in proprietor numbers and entrepreneurship rates to reassess the 'decline of Victorian entrepreneurship', onset of the 'U'-shaped trough of the twentieth century, the 'climacteric' of 1901, and compositional changes by sector and sex. There is strong sector and gender diversity, with changes in female participation major drivers of overall trends. Proprietor numbers show slow increases of employers, and rapid rise and then decline of own-account, with a turning point after 1901. The methodology and turning point is compared and confirmed against the 1921 census and national and local trade directories. Current affilition for Piero Montebruno: Geographical Research Economist at the Centre for Economic Performance, London School of Economics and Political ScienceSupplemental data for this article is available online at https://doi.org/10.1080/00076791.2021.1894134 .